The Efficacy and Safety of Low Dose versus Usual Dose of Hyoscine During Endoscopic Retrograde Cholangiopancreatography: A Randomized Clinical Trial - Salmanroghani H; Mirvakili M; Mirjalili M; Baghbanian M; Salmanroghani R (Dove Medical Press, 2020)
Hassan Salmanroghani,1 Massoud Mirvakili,1 Mahtabalsadat Mirjalili,2 Mahmud Baghbanian,1 Roham Salmanroghani3 1Department of Internal Medicine, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 2Department of Clinical Pharmacy, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran; 3Medical Student Research Center, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Hassan SalmanroghaniShahid Sadoughi Hospital, Yazd, IranTel +983538224000Fax +983538224100Email salmanroghani@hotmail.comPurpose: To evaluate the efficacy and safety of low dose versus usual dose of Hyoscine during endoscopic retrograde cholangiopancreatography (ERCP).Patients and Methods: This randomized, open-label clinical trial included 282 patients undergoing ERCP who had duodenal peristalsis interfering with cannulation. Patients were randomly divided into two groups: Group one and two received low (5 mg) and usual (10 mg) dose of Hyoscine, respectively. Cardiovascular service consultation was performed for all patients before entering the study and performing ERCP. Hyoscine was injected intravenously, and the spasmolytic effect of the drug was assessed while the papilla was in a completely enface view. The time interval between cessation of peristalsis and its further onset was recorded by the chronometer. Also, patient’s heart rate and blood pressure were monitored during ERCP by digital monitoring.Results: The results showed no statistically significant differences in the mean duration of peristalsis, the duration of the antispasmodic activity and the time required to increase the heart rate between two groups (P=0.38, P=0.48, P=0.32, respectively). No significant differences were observed regarding the average of heart rate and mean arterial blood pressure (MAP) before drug administration between the two groups (P=0.182 and P=0.29, respectively), but after the drug administration, tachycardia and hypotension were significantly higher in the second group (P=0.007 and P=0.001, respectively). There was no statistically significant difference in the frequency of arrhythmia between two groups (P=0.08). The results also showed that tachycardia and hypotension occurred more frequently in men and elderly patients (P < 0.05).Conclusion: A low dose of Hyoscine is as effective as the usual dose and its side effects such as alteration in blood pressure and heart rate are much fewer, especially in men and elderly patients.Keywords: hyoscine, ERCP, peristalsis, spasmolytic effect, cardiovascular abnormalities